Influence of TiO2 Nanoparticle Doping on the Splay and Bend Elastic Constants of the Nematic Liquid Crystal 4′-butyl-4-heptyl-bicyclohexyl-4- carbononitrile, CCN47 - Walton, H. G. (Molecular crystals and liquid crystals (Philadelphia, Pa. : 2003), 2013)
Measurements are reported of the splay and bend elastic constants, and the Freédericksz threshold voltages of the nematic liquid crystal 4′-butyl-4-heptyl-bicyclohexyl-4-carbononitrile (CCN47) doped with low concentrations of titanium dioxide (TiO 2 ) nanoparticles. No measurable impact was found on elastic properties at frequencies of a few kilohertz, in contrast to literature reports of substantial threshold voltage changes observed for nematics subject to low (Hz) frequency applied electric fields. The results support the view that such effects are likely due to ionic influences rather than changes to elastic properties.